Influence of soundscape and interior design on anxiety and perceived tranquillity of patients in a healthcare setting. (March 2016) - Watts, Greg; Khan, Amir; Pheasant, Rob
Abstract: Tranquillity characterized by a pleasant but calming environment is often to be found in natural environments where man-made noise is at a low level though natural sounds can be relatively high. Numerous studies have shown a link between such restorative environments and hospital recovery rates, stress reduction, longevity, pain relief and even how the brain processes auditory signals. In hospitals and primary care facilities there is a need to improve patient waiting rooms as current designs are largely based solely on medical need. There are often long waits in such spaces and patients are coping with the stress and anxiety caused by their medical condition. Attention should therefore be given to creating "restorative environment" as a component to their medical treatment. The study describes the effects of introducing natural sounds and large images of natural landscapes into a waiting room in a student health center. Using self reported levels of anxiety and tranquillity it was possible to assess the impact that these targeted auditory and visual interventions had in affecting the quality of the patient experience. Following the changes results show that levels of reported tranquillity were significantly improved but there were smaller change in reported reductions in anxiety.